Impact of Induced Moods, Sensation Seeking, and Emotional Contagion on Economic Decisions Under Risk - Efimov, Kirill; Ntoumanis, Ioannis; Kuskova, Olga; Kadieva, Dzerassa; Panidi, Ksenia; Kosonogov, Vladimir; Kazanina, Nina; Shestakova, Anna; Klucharev, Vasily; Jääskeläinen, Iiro P. (Frontiers in Psychology, 2022)
In addition to probabilities of monetary gains and losses, personality traits, socio-economic factors, and specific contexts such as emotions and framing influence financial risk taking. Here, we investigated the effects of joyful, neutral, and sad mood states on participants’ risk-taking behaviour in a simple task with safe and risky options. We also analysed the effect of framing on risk taking. In different trials, a safe option was framed in terms of either financial gains or losses. Moreover, we investigated the effects of emotional contagion and sensation-seeking personality traits on risk taking in this task. We did not observe a significant effect of induced moods on risk taking. Sad mood resulted in a slight non-significant trend of risk aversion compared to a neutral mood. Our results partially replicate previous findings regarding the presence of the framing effect. As a novel finding, we observed that participants with a low emotional contagion score demonstrated increased risk aversion during a sad mood and a similar trend at the edge of significance was present in high sensation seekers. Overall, our results highlight the importance of taking into account personality traits of experimental participants in financial risk-taking studies.